Sistem Muzara’ah Dalam Membangkitkan Ekonomi Masyarakat Desa Paringgonan Kecamatan Ulu Barumun Kabupaten Padang Lawas - Mahmudin Hasibuan; Asrul Hamid; Muhammad Safa'at; Andri Muda Nst (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2023)
Abstract: This research aims to find out the law of building a mosque with zakat in Islamic law. And to know that the mosque is included in the mustahik zakat group according to Islamic law. This research was conducted using field research, using descriptive qualitative research methods. Descriptive research is research conducted to collect data, test, or answer questions regarding the latest status of an object being studied. So this research can be concluded from the results of documentation, interviews and direct observation at the location. The research results show that the muzara'ah system that applies in Paringgonan Village, Ulu Barumun District, Padang Lawas Regency is in accordance with customs that do not conflict with the Al-Qur'an and Hadith. Because it is carried out on the basis of agreement and consent between the land owner and the land cultivator. And from an Islamic economic perspective, the muzara'ah system that applies in Paringgonan village is based on the principle of volunteerism, the principle of justice, and the principle of mutual assistance. That the muzara'ah system can revive the economy of the people of Paringgonan Baru Village, Ulu Barumun District, Padang Lawas Regency according to the percentage of each share. Without any harm to either party. Like Mr. Amin and Mr. Sutejo, as well as Mr. Zeri, before joining this system, his average income was only sufficient for his daily needs. Because the source of income for sharecroppers apart from doing muzara'ah cooperation is only as casual laborers whose results are uncertain. Meanwhile, Mr. Amin is able to provide for his daily life. Therefore, the people of Paringgonan Village, especially sharecroppers, are looking for additional funds or income through muzara'ah contracts or often called paroan paddy fields to increase their income so that sharecroppers can revive the economy of their respective families.